The Heath of The Peri-Implant Phenotype after Immediate Insertion and Loading of One-Piece and Two-Piece Dental Implants in the Anterior Region. A Clinical and Cone-Beam Computed Tomographic Study - Assadawy, Mohamed Ismail; Rifaie, Ahamed Osama (European Journal of General Dentistry, 2022)
Objective This study aimed to provide an inclusive comparison between the peri-implant phenotype of immediately placed in fresh extraction socket one-piece and two-piece implants with immediate loading in the anterior region.Materials and Methods Twenty-two patients with a mean age of 36 ± 4.6 (4 males and 18 females)) were randomly allocated to the one-piece and the two-piece groups. Each patient had one immediate implant placement with immediate loading by provisional restorations. Gingival Index, Peri-implant Probing depth, Papilla Presence Index, and, Implant Quality Score were recorded at 3, 6, 9 months, and 18 months. Cone beam computerized tomography is utilized to assess peri-implant bone for 1 year.Statistical analysis A two-sample t-test was used to compare the two groups.Results Both groups showed similar clinical presentations. For group two, Gingival Index, Papilla Presence Index, Peri-implant Index, Implant Quality Score, and eri-implant bone level showed statistically significant improvement. Group one showed a non-significant increase in bone density.Conclusions The peri-implant phenotype showed more predictable treatment outcomes in the context of health and esthetics in two-pieces than in one-piece.
Keywords: extraction socket; one-piece dental implants; esthetics; peri-implant phenotype.